Labyrinth lost - Córdova, Zoraida (Córdova, Zoraida. Brooklyn Brujas, 2016)
"Alex is a bruja and the most powerful witch in her family. But she's hated magic ever since it made her father disappear into thin air. When a curse she performs to rid herself of magic backfires and her family vanishes, she must travel to Los Lagos, a land in-between as dark as Limbo and as strange as Wonderland, to get her family back"--